2021
DOI: 10.1186/s12935-021-01779-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of DNA repair-related genes predicting pathogenesis and prognosis for liver cancer

Abstract: Background Liver cancer (LC) is one of the most fatal cancers throughout the world. More efficient and sensitive gene signatures that could accurately predict survival in LC patients are vitally needed to promote a better individualized and effective treatment. Material/methods 422 LC and adjacent normal tissues with both RNA-Seq and clinical data in TCGA were embedded in our study. Gene set enrichment analysis (GSEA) was applied to identify genes … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…31 There were also bioinformatic studies implying ZWINT as a prognostic indicator of HCC, even an independent one. 7,32 Consistently, we found ZWINT was significantly upregulated in various cancers including HCC, compared with the corresponding normal controls. We observed ZWINT overexpression significantly indicated the advancement of pathological stages, histological grades, and worse survivals of HCC patients.…”
Section: Discussionsupporting
confidence: 73%
“…31 There were also bioinformatic studies implying ZWINT as a prognostic indicator of HCC, even an independent one. 7,32 Consistently, we found ZWINT was significantly upregulated in various cancers including HCC, compared with the corresponding normal controls. We observed ZWINT overexpression significantly indicated the advancement of pathological stages, histological grades, and worse survivals of HCC patients.…”
Section: Discussionsupporting
confidence: 73%
“…The mutation of UPF3B causes multiple psychiatric illnesses, such as intellectual disability (ID) and schizophrenia (SCZ) [ 19 ]. Studies also suggest the UPF3B can be used as factors of gene models to predict tumor progression in various types of tumors, including esophageal cancer, liver cancer [ 20 , 21 ]. However, its potential action in cancer has not been extensively studied.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is a heterogeneous type of cancer that varies vastly in clinical outcome and response to therapy. Although several studies have identified important molecular classes in HCC, uncertainty remains regarding their associations with outcomes and their complex interaction with liver regenerative processes [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Recently, our lab defined three distinct molecular-based subpopulations of HCC tumors, namely HCC, Blast-Like, and CCA-like, based on gene expression similarity to cholangiocarcinomas and hepatoblast cells [ 14 ].…”
Section: Introductionmentioning
confidence: 99%